The Controversy Surrounding the Recognition of Foreign Degrees: A Case Study of Gibran Rakabuming Raka in the Context of Indonesian Educational Policy: Polemik Penyetaraan Ijazah Luar Negeri: Studi Kasus Gibran Rakabuming Raka dalam Perspektif Kebijakan Pendidikan di Indonesia - Roshiana Nishfi (Yayasan Cerdas Pedia Indonesia, 2025)
This study examines the structural and procedural challenges in the recognition of foreign academic qualifications under Indonesian educational policy, using the controversy surrounding Gibran Rakabuming Raka’s degree equivalency as a case study. Drawing on policy analysis and thematic document review, the research identifies significant ambiguities in the implementation of the Indonesian National Qualifications Framework (KKNI) and overlapping authorities between the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs. The case highlights how non-traditional programs, such as foundation pathways, are inconsistently classified and legally equated with vocational secondary credentials. Public misperceptions and politically driven narratives further erode institutional trust despite official clarifications. Comparative insights from the United States and Singapore underscore the need for a more transparent, harmonized regulatory model that accommodates modern learning pathways. The findings call for streamlined procedures, a unified regulatory framework, and accessible public registries to ensure credible, efficient, and equitable foreign degree recognition in Indonesia.